IMPACT OF SOCIAL SUPPORT ON MENTAL HEALTH PROBLEMS OF PATIENTS WITH HEPATITIS C IN DISTRICT GUJRAT, PAKISTAN - Shafiq, Sameera; Aslam, Sadia (Journal of Postgraduate Medical Institute, 2021)
Objective: To find out the effects of different levels of social support on mental health problems. Methodology: This cross-sectional survey was conducted on 202 purposively selected, diagnosed patients of chronic hepatitis C, from various hospitals and private clinics situated in Gujrat. Urdu version of Depression, Anxiety, Stress Scale (DASS) developed by Lovibond et al. and Social Support Scale (SSS) was used to collect data. Frequencies and percentages, Pearson Product moment correlation and Multiple Analysis of Variance (M-ANOVA) were calculated with SPSS 21 to measure the impact of levels of social support on depression, anxiety, and stress of the patients. Results: There was a significant negative correlation between social support and depression (r=-0.54, p<0.001), anxiety (r=-0.53, p<0.001), and stress (r=-0.34, p<0.001) among patients with chronic hepatitis C. Multivariate analyses of variance (MANOVA) revealed a significant impact of levels of social support provided to these patients on their psychological outcomes in terms of depression, anxiety, and stress (F (6, 394) = 9.15, p<0.0005; Wilk's A =0.77, partial É³² = 0.12). Conclusion: The levels of social support significantly affect mental health problems; depression, anxiety, and stress in patients with chronic hepatitis C.